Analyzing accuracy and accessibility in ICT ethical scenario context - Masrom, Maslin; Ismail, Zuraini; Anuar, Rashidah Nural; Hussein, Ramlah; Mohamed, Norshidah (2010)
Recently, the development of Information and Communication Technology (ICT) is indispensable to life.The utilization of ICT has provided advantages for people, organizations, and society as a whole. Nevertheless, the widespread and rapid use of ICT in society has exacerbated existing ethical issues or dilemmas, and also led to the emergence of new ethical issues such as unauthorized access, software piracy, internet pornography, privacy protection, information gap, and many others. Therefore, the aim of this paper is to discuss several issues of the ICT ethics. It will focusing on two major issues, that is, data accuracy and accessibility.Several computer ethics scenarios that relate to the data accuracy and accessibility are presented, and the results of analysis are then discussed.